Karakteristik Kepemimpinan Tranformasional di Lingkungan Pesantren - Syaikhul Hakim; Binti Maunah (Institut Agama Islam Al-Hikmah Tuban, 2023)
Abstract, This research aims to describe the characteristics of transformational leadership in the Islamic boarding school environment. Islamic boarding schools are educational institutions that are undergoing a transformation from traditional education to modern education. Transformational leadership in Islamic boarding schools focuses on the charismatic and affective elements of leadership. Islamic boarding school leaders who adopt transformational leadership usually have the characteristics of being visionary, inspiring, motivating, empowering, and promoting self-acceptance. They also create an inclusive culture based on Islamic values ​​that encourages loyalty, honesty, responsibility, example, justice and cooperation. The research method used is qualitative research with a case study approach. Data was collected through observation, interviews and documentation studies. Data analysis was carried out qualitatively using techniques such as data condensation, data presentation, and drawing conclusions. The research results show that transformational leaders in the Islamic boarding school environment have a vision that provides direction and meaning to their followers. They are able to communicate high expectations to followers and understand the needs of subordinates and empower them. In conclusion, transformational leadership in the Islamic boarding school environment is an effective leadership model in encouraging the growth and development of students. Transformational leaders create a positive and productive learning environment, building the next generation who are skilled, independent, and play an active role in society. It is hoped that the application of transformational leadership characteristics can increase the competitiveness of Islamic boarding schools and the overall quality of Islamic boarding school education. Keywords: Transformational leadership, Islamic boarding school